Implementasi Putusan Mahkamah Konstitusi Nomor 56/Puu-Xvii/2019 Bagi Calon Kepala Daerah Berstatus Mantan Terpidana Korupsi Dipilih Kembali dalam Pemilihan Kepala Daerah Tahun 2020 - Caka Adidarma; Sunny ummul Firdaus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
This legal research aims to find out the implementation of the decision of the Constitutional Court No. 56/PUU-XVII/2019 for regional head candidates, especially former convicted of corruption who will follow back in the regional head elections in 2020 and the legal consequences of the ruling. This legal research uses normative or doctrinal legal research methods that are prescriptive. The research approach the authors use is the legal approach and the case approach. The data types used are primary and secondary data. Primary data is obtained from legislation while secondary data is obtained through literature studies, namely books, journals, and scientific articles.The implementation of constitutional court decision No. 56/PUU-XVII/2019 granted the application related to the conditions for candidates for regional heads, especially former corruption convicts who are required to wait for a period of 5 years after serving a prison term based on a court ruling with permanent legal force. In contesting the simultaneous elections in 2020 the verdict has not been able to be implemented maximally because there are several candidates for regional heads of former corruption convicts who do not comply with the conditions of candidacy can run in the 2020 election. Among others in North Nias Regency, South Lampung Regency, Dompu Regency, Boven Digoel Regency, and Bengkulu Province. Among these areas, the candidate for regional head is a former corruption convict who won the contestation of elections is Boven Digoel Regency. The decision of MK No. 56/PUU-XVII/2019 resulted in the change of PKPU No. 9 of 2020 article 4 paragraph (1) letter g about for ex-convicts who have completed their sentence must honestly or openly present to the public regarding their identity background as former convicted of corruption. As a result of PKPU No.9 of 2020, the arrangement of candidates who are inmates raises special conditions for the nomination of elections in 2020 who must wait for a five-year time lag period after serving their criminal sentences.